2021
DOI: 10.1111/exd.14428
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular hand eczema transcriptome analysis provides insights into its pathophysiology

Abstract: Hand eczema is a common inflammatory skin condition of the hands whose pathogenesis is largely unknown. More insight and knowledge of the disease on a more fundamental level might lead to a better understanding of the biological processes involved, which could provide possible new treatment strategies. We aimed to profile the transcriptome of lesional palmar epidermal skin of patients suffering from vesicular hand eczema using RNA-sequencing. RNA-sequencing was performed to identify differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 70 publications
1
31
0
1
Order By: Relevance
“…This positive effect on HE has also been shown in several case reports in isolated, nonatopic HE, including vesicular HE, hyperkeratotic HE, allergic contact dermatitis, and ICD 7,18 . Furthermore, in a recently published study, in which we analysed the transcriptome of vesicular HE through RNA‐sequencing, it was found that IL4R was also highly upregulated in lesional HE skin compared with healthy control skin 19 . This suggests that the IL‐4/IL‐13 pathway might also be involved in isolated HE.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This positive effect on HE has also been shown in several case reports in isolated, nonatopic HE, including vesicular HE, hyperkeratotic HE, allergic contact dermatitis, and ICD 7,18 . Furthermore, in a recently published study, in which we analysed the transcriptome of vesicular HE through RNA‐sequencing, it was found that IL4R was also highly upregulated in lesional HE skin compared with healthy control skin 19 . This suggests that the IL‐4/IL‐13 pathway might also be involved in isolated HE.…”
Section: Discussionsupporting
confidence: 78%
“…7,18 Furthermore, in a recently published study, in which we analysed the transcriptome of vesicular HE through RNA-sequencing, it was found that IL4R was also highly upregulated in lesional HE skin compared with healthy control skin. 19 This suggests that the IL-4/IL-13 pathway might also be involved in isolated HE. These overlaps in pathways between the AD transcriptome and HE transcriptome, and results from previously published case reports and case series in isolated HE, hold promise for dupilumab to be a suitable treatment for moderate to severe CHE in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, transcriptomic profiles of human skin diseases used for comparison are mostly derived from human hairy skin – a difference that needs to be taken into account when interpreting the presented comparisons between mouse and human skin. This is why we additionally selected transcriptomic studies on skin diseases affecting human glabrous skin, that is, palms and soles, such as handfoot psoriasis ( Ahn et al, 2018 ), palmoplantar pustulosis ( McCluskey et al, 2022 ), and vesicular hand eczema ( Voorberg et al, 2021 ). Among top gene signatures presented in glabrous skin datasets (2498 DEGs), 928 proteins were quantified in our paw skin datasets and 96 of them showed age and/or sex dependency including several collagens ( Figure 6—source data 3 ; examples are marked with ‘#’ in Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Read sequences were already trimmed before by BaseClear B.V. (Leiden, The Netherlands) as previously described. 5 The trimmed read sequences were subsequently aligned to the human reference genome sequence (GRCh38; Ensembl release 103) using STAR (version 2.7.8a). 7 For more details on the settings used in this study, see Supporting information.…”
Section: Transcriptome Datamentioning
confidence: 99%
“…5 Both diseases exhibit an upregulation of genes involved in keratinocyte host defence, inflammation, and immune signalling, while simultaneously downregulated genes are involved in skin barrier function. 5 However, the DEGs that differentiate VHE from AD are unknown. Characterization of these DEGs would provide more insight into the pathogenesis of HE.…”
mentioning
confidence: 99%